Perancangan Interior Restoran Tradisional Makassar - Lidwina Tham Djaya; Lintu Tulistyantoro (Intra, 2014)
Traditional culture has potential to attract tourists to come to one city. But along with the times, the traditional culture will extinct so we need the effort to preserve them. In this day, culture and culinary is not an easy thing to find, more over just for a vacation. This Makassar’s restaurant interior desaign purposes is to give an information about Makassar’s culture through interior design that applied to the restaurant and to gives a taste of traditional cuisine of Makassar. Indonesia has a lot of culture, one of them is Makassar culture. For a foodies, this would be very nice to know about Makassar Traditional cuisine.